Love's abiding joy - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House Publishers, 2003)
Clark and Marty visit their daughter Missie and her husband Willie in the far West and meet their two little grandsons, but their faith is tested once again when the visit is marred by a tragic accident.
Family -- Birthday Dinner -- Planning -- The City -- The Real Journey Begins -- Arrival -- Catching Up -- Marty Meets Maria -- The Rescue -- A Day of a Million Years -- Struggles -- Juan -- Adjustments -- Growing -- Moving -- Winter -- Jedd -- From Death to Life -- Plans and Farewells -- Homeward Bound.
Keywords: Davis family (Fictitious characters : Oke) -- Fiction; Women pioneers -- Fiction; Grandparents -- Fiction; Christian fiction; Domestic fiction; Western stories